2016
DOI: 10.1371/journal.pone.0167404
|View full text |Cite
|
Sign up to set email alerts
|

Meningococcal Carriage in Military Recruits and University Students during the Pre MenB Vaccination Era in Greece (2014-2015)

Abstract: PurposeThe aim of the study was to estimate the meningococcal carriage rate and to identify the genotypic characteristics of the strains isolated from healthy military recruits and university students in order to provide data that might increase our understanding on the epidemiology of meningococcus and obtain information which helps to evaluate the potential effects on control programs such as vaccination.,MethodsA total of 1420 oropharyngeal single swab samples were collected from military recruits and unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
8
16
1
1
Order By: Relevance
“…This study identified a carriage prevalence of 16% for N. meningitidis in those entering a military college in the Russian Federation, and similar rates have been seen in recruits entering a military setting in Greece (15%) (Tryfinopoulou et al, 2016) and Poland (16-24%) (Tyski et al, 2001), with lower carriage rates seen for recruits entering a military setting in Turkey (4.2%) (Celal Basustaoglu et al, 2011) and Iran (8%) (Ataee et al, 2016) and professional soldiers in Poland (5.2% and 9.6%) (Korzeniewski et al, 2017;Korzeniewski et al, 2015). It was anticipated that the carriage rate would increase after recruitment while the recruits resided in a semi-closed environment as these populations are at higher risk for outbreaks of meningococcal disease (Aguilera et al, 2002;Brundage et al, 2002; National Foundation for Infectious Diseases (NFID), 2017); while a study of the change in carriage rate in students identified a rapid increase on entering university (Neal et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This study identified a carriage prevalence of 16% for N. meningitidis in those entering a military college in the Russian Federation, and similar rates have been seen in recruits entering a military setting in Greece (15%) (Tryfinopoulou et al, 2016) and Poland (16-24%) (Tyski et al, 2001), with lower carriage rates seen for recruits entering a military setting in Turkey (4.2%) (Celal Basustaoglu et al, 2011) and Iran (8%) (Ataee et al, 2016) and professional soldiers in Poland (5.2% and 9.6%) (Korzeniewski et al, 2017;Korzeniewski et al, 2015). It was anticipated that the carriage rate would increase after recruitment while the recruits resided in a semi-closed environment as these populations are at higher risk for outbreaks of meningococcal disease (Aguilera et al, 2002;Brundage et al, 2002; National Foundation for Infectious Diseases (NFID), 2017); while a study of the change in carriage rate in students identified a rapid increase on entering university (Neal et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…The serogroup composition at Day 1 was also diverse, which may be related to the large geographical catchment area for these new recruits (Claus et al, 2005). This diversity in serogroup composition was also seen for other studies of recruits entering the military setting (Ataee et al, 2016;Celal Basustaoglu et al, 2011;Tryfinopoulou et al, 2016;Tyski et al, 2001). By Day 60 the diversity of serogroup composition had reduced, with a change in serogroup distribution compared to baseline, with many of the identified isolates belonging to serogroup W. Of the serogroup W isolates that were sequenced the vast majority were ST11, and one ST53 isolate was detected at Day 60.…”
Section: Discussionsupporting
confidence: 62%
“…The present study confirmed that serogroup B was predominant among carriers; it was mostly represented by ST-41/44CC. Similar sequencing results were observed in Greece in a population of military recruits (Tryfinopoulou et al 2016). Hypervirulent clonal complexes ST-213CC, ST-213CC, which have been observed in Poland, were also found in the study partici pants.…”
Section: Discussionsupporting
confidence: 87%
“…Fifteen studies that sampled only university students met the inclusion criteria. Six studies were cross-sectional studies (Aliyu and Olayinka, 2017;Bali et al, 2017;Rizek et al, 2016;Rodrigues et al, 2015;Rodriguez et al, 2014;Tryfinopoulou et al, 2016;Takahashi et al, 2016), six were repeat cross-sectional studies with a nested cohort (either intentional or unintentional) (Ala'aldeen et al, 2011;Breakwell et al, 2018;Durey et al, 2012;McNamara et al, 2017b;Oldfield et al, 2017;Soeters et al, 2017), two were cohort studies (Bidmos et al, 2011;Gilca et al, 2013), and one was a randomized controlled trial investigating the impact of vaccination on carriage (Read et al, 2014). The majority of studies were conducted in the region of the Americas (n = 6) or the European region (n = 6), and no study was identified from the Eastern Mediterranean region.…”
Section: University Studentsmentioning
confidence: 99%
“…Malaysia (Memish et al, 2017) prevalent capsular groups identified were C (46.3%), Y (21.1%), and B (1.5%), respectively, at baseline (Table 2). Seven studies assessed risk factors associated with increased carriage among university students, the methodology of which is detailed in Supplementary material Table S7 (Aliyu and Olayinka, 2017;Rodriguez et al, 2014;Tryfinopoulou et al, 2016;Breakwell et al, 2018;Durey et al, 2012;McNamara et al, 2017b;Soeters et al, 2017). Risk factors investigated included demographic data and social behaviours, such as age, sex, smoking, recent respiratory infections, and attending crowded social settings.…”
Section: University Studentsmentioning
confidence: 99%